Capacity of Autotomy and Postautotomy Movement of Original and Regenerated Tail of Lizards (Mabouya multifasciata Kuhl) - Luthfi, Muhammad Ja’far; Soesilo, Nyoman Puniawati; Santoso, Raliandana Louise (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Lizards have the ability to shed their tails as a defence mechanism, known as autotomy. The tails will regenerate after automomy. Anatomical difference between original and regenerated tail could have resulted in the difference of capacity of autotomy and postautotomy tail movement. The aims of the research were to study the capacity of autotomy and postautotomy movement of original and regenerated tail of lizard. Comparation of the capacity of autotomy and postautotomic movement between original and the regenerated tail was studied using three groups of lizard, namely group of lizard with original tail (10 lizards), eight weeks regenerated tail group (10 lizards), and twelve weeks regenerate tail group(10 lizards). All groups received same treatment. The lizards were hold on the proximal part of tail with tweezers until autotomy has taken place, and the duration to autotomy and postautotmy movement were recorded. The result of the study revealed that the capacity of autotomy and the postautotomy movement were lower in regenerated tail compare to those of the original one.